Evaluación de 3 soluciones nutritivas en acelga beta vulgaris var. cicla mediante el sistema hidropónico raíz flotante bajo invernadero - Barrezueta Ortega, Dustin Stalin (2010)
This work on nutrient solutions in chard (Beta vulgaris var. cicla.) Using the following floating hydroponic system under greenhouse conditions, was held at the Faculty of Agricultural Sciences at The Technical University of Machala, located in the parish Change Region Machala, province of El Oro, Ecuador. Its objectives were to determine the best nutrient solution, establishing the duration of the stages of crop development, according to the percentage of shadow and perform economic analysis. The area used for the test was 10 m2 greenhouse, hydroponic system for floating root containers were used were 0.50 m long by 0.50 m wide and a height of 0.15 m, this technique is to keep the roots of the chard submerged in nutrient solutions and with the air that is held on a plumafón; oxygenation gave it with a compressor that is activated automatically with a timer. Three solutions were tested with an initial concentration T1, less than 50% were T2 and 50% over Q3 tested against a witness based NPK. The statistical design used was completely randomized to three treatments and ten repetitions witness. Present the following stages of crop development chard: Early stage (21 days), growth phase of development (41 days), mid-term phase (10 days) and final phase (5 days). Of the estimated nutrient solutions, the best treatment was T2 with the economic analysis showed a net profit of $ 511.53 / 10m2 for a B / C ratio of 2.15 and a return of 115.04%, which is be profitable for two years.